Lost archaeological heritage: virtual reconstruction of the medieval castle of San Salvador de Todea - Patricia Valle Abad; Adolfo Fernández Fernández; Alba Antía Rodríguez Nóvoa (Virtual Archaeology Review)
The medieval castle of San Salvador de Todea constitutes a remarkable paradigm for the rock castles of Galicia and the northwest of Spain, attending to its features but also to the destruction it was subjected. The hill where it stands was the object of various archaeological interventions led from 2016 to 2018, that identified the site as a medieval fortress and recovered part of its structures. Being one of few medieval castles of the 12th-15th centuries in Galicia subjected to consecutive interventions and actively studied. Although the excavations provided an important amount of information about the chronology, distribution, material culture and even diet of the inhabitants, the interpretation of the castle is really complex. The preserved remains correspond to the foundations of the structures, mainly a few walls and a high amount of carvings scattered over the hill. This paper gathers the results of the investigation developed to create a reconstructive hypothesis for the castle and its materialization in a digital model, as a way to interpret and understand its structure. To achieve this aim, we combined the analysis of the archaeological data and the geomorphology of the own hill, with the study of fortresses with similar disposition and chronology, and the appliance of architectonical rules, in a multidisciplinary study. In order to generate a reasonable, justified and scientific model of the castle, useful as an instrument to study and comprehend this type of construction. The resulting model shows the disposition, height and entity of the structures that conformed to the castle, the transit areas and indoor spaces, and provides new data to calculate the visibility and predominance of the construction over the landscape, among others. Finally, to ensure the rigour and scientific approach of the reconstruction, we utilised a scale of certainty level to show the results, along with photorealistic textures to recreate the probable aspect of the castle. Highlights: - Virtual reconstruction of a Late Medieval rock castle, from the archaeological remains recorded during the excavations of the site and the comparison with similar structures. - Overview of the reconstruction methodology, decision-making process and resulting constructive hypothesis, with a detailed description of the level of certainty of each part. - Multidisciplinary approach to achieve a scientific model that helps to understand the castle distribution and its importance on the control of the landscape.